Comparison of yoga and aerobic trainings for improving mental health of divorced women - Afrooz Mousavi; Leila Moghtader (Gonabad University of Medical Sciences, 2017)
Exercise is an acceptable method for improving and maintaining the physical and emotional health. The aim of the present study was to compare the effectiveness of yoga training program and aerobic exercise on the mental health of divorced women. Two experimental groups and one control group were employed in this quasi-experimental study. The number of 30 divorced women was randomly divided into three groups. The experimental groups involved in yoga (n=10) and aerobics training (n=10) and received 16 exercise sessions for two months. The control group (n=10) received no training. General health questionnaire-28 was employed to evaluate the mental health of participants. Covariance analysis was used as the statistical method. The obtained results indicated that the intervention improved significantly the mental health indices in the intervention groups of yoga and aerobics. In comparison of the effectiveness of yoga and aerobics exercises, the results showed that there is not significant difference between the effectiveness of yoga and aerobics. Therefore, the two methods of exercise are effective on improving the mental health